A study of the architectural aspects of transmigration settlements in Seputih Raman - Lampung - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT The impact of the differing ways of lift of transmigrants_ on the subsequent development of their settlements is a unique phenomenon. This paper presents the results of analysis based on observation and measurement of the physical environments in Seputih Raman transmigration villages in Lampung, concerning particularly the architectural aspects developed in these settlements. Employing descriptive and univariate analyses, the study concludes that the transmigrants have modified their initial housing provision to suit their aspirations and ways of lift, in line with their ethnic origin. Analysis also revedis that Balinese villages and houses have. distinctive features, forms, and spatial formations